Development of lipid nanoparticles loading thymol and Lippia origanoides essential oil in inclusion complexes with cyclodextrin - Pires, Felipe de Queiroz (2018)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Ciências da Saúde, Programa de Pós-Graduação em Ciências Farmacêuticas, 2018.